Menelusuri Kitab Taurat melalui Dua Perspektif: Sosio-Politis dan Theokrasi-Teologis - Padan, Stefanus; Masinambow, Yornan (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract: This article explores the Torah through two perspectives, namely socio-political and theocratic-theological, using a literature study approach. Socio-politically, the Torah is understood as a historical document that reflects the social and political context of ancient Israel, while the theocratic-theological perspective sees it as a divine revelation that governs moral and spiritual life. The research methodology involves a literature analysis of academic sources related to the history, social structure, and theological values in the Torah. The results of the discussion show that these two approaches complement each other in providing a comprehensive understanding of the Torah, both as legal guidance and divine revelation. The article concludes that combining the two perspectives can enrich the theological discourse and relevance of the Torah in the modern context. Abstrak: Artikel ini mengeksplorasi Kitab Torah melalui dua perspektif, yaitu sosio-politis dan teokrasi-teologis, dengan pendekatan studi kepustakaan. Secara sosio-politis, Kitab Torah dipahami sebagai dokumen historis yang mencerminkan konteks sosial dan politik bangsa Israel kuno, sementara perspektif teokrasi-teologis melihatnya sebagai wahyu ilahi yang mengatur kehidupan moral dan spiritual serta merupakan bagian dari karya keselamatan Allah. Metodologi penelitian melibatkan analisis literatur dari sumber-sumber akademis terkait sejarah, struktur sosial, dan nilai-nilai teologis dalam Torah. Hasil pembahasan menunjukkan bahwa kedua pendekatan ini saling melengkapi dalam memberikan pemahaman yang komprehensif mengenai Torah, baik sebagai pedoman hukum maupun wahyu ilahi. Artikel ini menyimpulkan bahwa penggabungan kedua perspektif dapat memperkaya diskursus teologis dan relevansi Torah dalam konteks modern.